2010
DOI: 10.1002/pola.24045
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of sulfonated crosslinked poly(2,6‐dimethyl‐1,4‐phenylene oxide) membranes for direct methanol fuel cells by using electron beam irradiation

Abstract: Sulfonated crosslinked poly(2,6‐dimethyl‐1,4‐phenlylene oxide) (PPO) were successfully fabricated via electron beam irradiation followed by sulfonation and evaluated for direct methanol fuel cell (DMFC) applications. The thermal and mechanical properties were improved by the formation of crosslinked networks in the PPO membranes. The sulfonated crosslinked PPO (CPPO) membranes exhibited better ion exchange capacity and proton conductivity than the Nafion 115. The methanol permeability of the sulfonated CPPO me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The synthesis of SPS-COOH was verified by several distinct peaks related with the sulfonic group at 1125À 1223 cm À1 and at around 3500 cm À1 . 31À33 The ratio of ÀCOOH functional groups to ÀSO 3 H functional groups was 1:0.68, measured by titration 34 and supported by zeta potential results (Figure S5). A homogeneous dispersion of SPS-COOH in the solution of the iron precursor derives from the electrostatic interaction between the strongly negatively charged groups (ÀCOOH, ÀSO 3 H) of SPS-COOH and iron ions (Fe 3þ ) in FeCl 3 solution, leading to adsorption of a sufficient amount of iron ions onto the spheres.…”
Section: Resultssupporting
confidence: 65%
“…The synthesis of SPS-COOH was verified by several distinct peaks related with the sulfonic group at 1125À 1223 cm À1 and at around 3500 cm À1 . 31À33 The ratio of ÀCOOH functional groups to ÀSO 3 H functional groups was 1:0.68, measured by titration 34 and supported by zeta potential results (Figure S5). A homogeneous dispersion of SPS-COOH in the solution of the iron precursor derives from the electrostatic interaction between the strongly negatively charged groups (ÀCOOH, ÀSO 3 H) of SPS-COOH and iron ions (Fe 3þ ) in FeCl 3 solution, leading to adsorption of a sufficient amount of iron ions onto the spheres.…”
Section: Resultssupporting
confidence: 65%
“…Their results also showed that the measured ionic conductivities were comparable to Nafion membranes. In another study, Lee et al obtained higher proton conductivity and lower methanol permeability in sulfonated crosslinked PPO membranes with 30.1% sulfonation degree in comparison with Nafion 115 systems [14]. Hasani-Sadrabadi et al reported that the observed methanol permeation in nanocomposite PEMs based on SPPO and organically modified montmorillonite clay was decreased compared to Nafion membranes [15].…”
Section: Introductionmentioning
confidence: 95%
“…The results suggested that the increasing IEC values are relative to water uptake of the SPNB/KH550/PWA membranes. 25 The IEC value ranges from 0.14 to 0.60 mequiv/g, increasing with increased PWA concentration in the feed, mainly attributed to the extra proton conductivity groups derived from PWA, resulting in the improved proton conductivity (discussed later).…”
Section: Resultsmentioning
confidence: 98%
“…The IEC values is an indication of sulfonic acid groups presented in a polymer matrix, which are responsible for the conduction of protons and thus is an indirect and reliable approximation for the proton conductivity. 25 The DS can be calculated from the corresponding IEC value of SPNB membranes using the following equation: The DS of the sprints SPNB can be calculated by IEC in this article is 0.28. As shown in Table 1, the same tendency to water uptakes also occurred in case of IEC values.…”
Section: Resultsmentioning
confidence: 99%